Desenvolvimento de sistema de teste laboratorial e metodologia para cromatografia gasosa acoplada a dessorvedor térmico e uso do octafluoropropano como traçador gasoso para o CO2 - Constant, Marcelo Jardim (2015)
Gas tracers are widely used to control effects in various areas of research, but its implementation has yet to be proven specifically in the case of CO2 monitoring in geological storage sites, so that the gas percolation system is designed to test the feasibility the use of gas tracers as indicators of CO2 in geological storage of carbon projects. The tracer gas injection system is a set of stainless steel connections, which occurs percolation of the tracer gas (octafluoropropane), mixed with carbon dioxide within a porous structure bench simulating the migration of this gas in the assembly. The gaseous tracers are markers that allow information about the migration of CO2 in porous media. Perfluorocarbons are gas tracers used in CO2 storage experiments. The octafluoropropane (C3F8) is a nonflammable fluorocarbon is commonly used in the semiconductor industry, but here in this paper was tested as a tracer for CO2. The bench injection system for gaseous tracer test was presented as a tool for a preliminary understanding of C3F8 tracer gas for CO2. The gases in the study were injected into a tube containing a porous medium, medium sand, to test the marker function of C3F8. Different injection times were tested and collected in thermal desorption tubes (CATs). The gas outlet of this tube were collected and analyzed by gas chromatography with an electron capture detector (ECD) coupled to a heat Desorption. Both C3F8 as CO2 were detected in all experiments indicating the possibility of C3F8 have passed through the porous medium with the CO2. The findings of this study and suggestions made based on it will help in further work related to the monitoring of CO2 and geological storage of carbon.